Case study on cooperative learning in a State School of Professional Education in Pentescoste-CE (Research, Society and Development, 2019)
Collaborative learning is a resource in the area of education, which arises from the need to introduce interactive methodologies between the student, or user, together with the teacher to establish searches, understanding and interpretation of information on specific subjects. Its relevance in the practice of a methodology that involves and awakens the youth protagonism in the region stands out here. For this research, we adopted the field survey, in which people are observed and questioned with the behavior if they want to know. Basically, we requested information from a significant group of people about the problem studied and then, through qualitative analysis, obtain the corresponding conclusions from the collected data. Thus, cooperative learning is a resource in the area of education, which arises from the need to introduce interactive methodologies between the student, or user, together with the teacher to establish searches, understanding and interpretation of information on specific subjects. Its relevance in the practice of a methodology in the school, that involves and awakens the youthful protagonism in the region stands out here.